1994
DOI: 10.1038/clpt.1994.73
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized comparison of the accuracy of computer-assisted versus GUSTO nomogram-directed heparin therapy

Abstract: Failure to adequately anticoagulate the blood of patients receiving recombinant tissue plasminogen activator (TPA) leads to greater rates of rethrombosis. In a multicentered, randomized trial in 51 patients we compared the ability to achieve and maintain therapeutic anticoagulation by use of computer-assisted heparin therapy or the GUSTO (Global Utilization of Streptokinase and TPA for Occluded Coronary Arteries) heparin nomogram guidelines in patients with myocardial infarction treated with recombinant TPA. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…9 12 16 Only two studies reported a power calculation. 11 15 Six studies reported adequate concealment of allocation (for example, random numbers in opaque envelopes),813 12 followed up more than 80% of patients, 8 12 13 1520 22 24 25 12 reported similar baseline measures between intervention and control groups, 8 – 14 16 1920 23 24 nine recorded that patient consent had been obtained, 810 15 18 – 20 22 23 and eight reported gaining approval from an ethics committee. 8 10 12 18 – 20 22 24 In one study the reviewers thought that there was little room for improvement because the performance of the health professional was adequate without the intervention 23…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 12 16 Only two studies reported a power calculation. 11 15 Six studies reported adequate concealment of allocation (for example, random numbers in opaque envelopes),813 12 followed up more than 80% of patients, 8 12 13 1520 22 24 25 12 reported similar baseline measures between intervention and control groups, 8 – 14 16 1920 23 24 nine recorded that patient consent had been obtained, 810 15 18 – 20 22 23 and eight reported gaining approval from an ethics committee. 8 10 12 18 – 20 22 24 In one study the reviewers thought that there was little room for improvement because the performance of the health professional was adequate without the intervention 23…”
Section: Resultsmentioning
confidence: 99%
“…Physiological control —Eight studies measured changes in control of a physiological parameter with computer support, 8 15 16 18 20 22 – 24 of which six showed significant benefit. 8 15 18 20 22 24 Computer support for anticoagulant control resulted in significant reductions in the time taken to achieve the desired prothrombin time22 and activated partial thromboplastin time 15.…”
Section: Resultsmentioning
confidence: 99%
“…CDS is also used to aide patient management independent of protocols by recommending suggestions for ventilator settings and weaning [41,42] , antibiotic assistance [43,44] , and medication dosing. Mungall et al [45] found significant improvement in achieving desired anticoagulation goals when using a CDS tool for heparin dosing following tissue plasminogen activator treatment in myocardial infarction compared to the standard nomogram. Blood glucose control is a commonly investigated area for support tools, and studies report more consistent target glucose levels and few adverse events with these tools [46][47][48] .…”
Section: Type Of Support Tool Example or Subjectmentioning
confidence: 99%
“…Ventilator fraction of inspired oxygen [41] Pressure support ventilation [42] Antibiotic recommendation [43,44] Blood glucose control [46][47][48] Sepsis [21] Heparin dosing after myocardial infarction [45] Research Mortality prediction [29] Prediction of fluid requirement [53] Predictive alerts for hemodynamic instability [49][50][51] Ventilator settings [76] Prediction of dialysis need [52] Insulin e-protocol [54,85] Pediatric and neonatal critical care Diagnostic ISABEL (www.isabelhealthcare.com) [59,86] SimulConsult (www.simulconsult.com) [87] MEDITEL pediatric diagnostic system [58] Outcome prediction and severity of illness [55][56][57] Alert and Reminder Drug interaction [62] Prescription errors and adverse drug events [18,61] Parenteral nutrition orders [61] NICU pulse oximeter [60] Protocol/Procedure Blood transfusions [63] Medications [61] Parenteral nutrition [64] Management Oxygen in ventilated newborns [68] Antibiotic recommendation [44,65] Blood glucose control [69] Medication information databases [88] Medication dosing calculators [61] Ventilator management in neonates [66,67] Research Virtual PICU (www.pi...…”
Section: Type Of Support Tool Example or Subjectmentioning
confidence: 99%
“…Because of the complex pharmacokinetics and pharmacodynamics of heparin, wide patient variability in anticoagulant response, and time delays between obtaining the blood sample and reporting aPTT results, 4 it is difficult to establish and maintain the therapeutic level of anticoagulation for each patient. Despite numerous efforts to improve the delivery of heparin, including heparin administration nomograms, 5 use of bedside aPTT devices, 4 and use of weight-adjusted 6 and computer-based algorithms, 7 recent trials have achieved only 30% to 35% of aPTTs that were within a 30-second target range. 8,9 In an attempt to improve heparin control, we developed and tested a prototype of the AutoHep system, which automatically acquires a venous blood sample, performs an aPTT measurement, and adjusts the heparin infusion rate to achieve an operator-selected aPTT target.…”
mentioning
confidence: 99%